2019
DOI: 10.1186/s12882-019-1515-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Efficacy, tolerability and safety of darbepoetin alfa injection for the treatment of anemia associated with chronic kidney disease (CKD) undergoing dialysis: a randomized, phase-III trial

Abstract: Following publication of the original article [1], the authors reported errors in the presentation of Tables 2, 4 and 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Epoetin alfa (recombinant human erythropoietin, rHuEPO) is a kind of erythropoiesis stimulating agent (ESAs) that is a primary choice for treating anemia in patients with CKD 2 . However, due to its short half‐life, its optimal administration route and dose remain controversial 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoetin alfa (recombinant human erythropoietin, rHuEPO) is a kind of erythropoiesis stimulating agent (ESAs) that is a primary choice for treating anemia in patients with CKD 2 . However, due to its short half‐life, its optimal administration route and dose remain controversial 3 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that darbepoetin alfa with a reduced dose frequency (once a week or biweekly) for treating anemia in CKD patients has similar efficacy and safety as epoetin alfa, 5–8 benefiting both patients and health care staff 3 . This study aimed to verify that the efficacy and safety of darbepoetin alfa are not inferior to epoetin alfa in maintaining Hb levels within the target range (10.0–12.0 g/dL) for the treatment of renal anemia in Chinese hemodialysis patients who are ESA‐naive.…”
Section: Introductionmentioning
confidence: 99%